Understanding Practices and Challenges of Developing Sustainable Research Software: A Pilot Interview - Feitosa, Daniela; von Flach, Christina; Costa, Joenio (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE); 2023: Anais do III Workshop de Práticas de Ciência Aberta para Engenharia de SoftwareDO - 10.5753/opensciense.2023.235677, 2023)
Research software is the software developed in universities and research laboratories as part of or to support their research. Research software sustainability, that is, the software's ability to last and continue to be supported over time, fosters long-term reproducibility. In this context, it is essential to understand and describe the current practice in universities and research laboratories concerning the development of sustainable research software. However, such information is seldom available, even for research projects funded by national agencies. In this paper, we present the results of a pilot interview study conducted with a research group in Applied Physics, whose members historically developed most of the supporting research software. We interviewed the leading investigator to collect information about his knowledge of open science, research software, and software engineering practices, the challenges and supporting factors to develop software, and possible efforts to make it sustainable. The pilot study allowed us to refine the study design to support a more comprehensive study with other groups at the same University.